Measuring the Success of Corporate Social Responsibility Programs: A Study of Indonesian Companies - Rosalina Rosalina (Pusat Studi Pembangunan dan Pemberdayaan, 2021)
Using a combination of qualitative and quantitative techniques, this research explores the impact that CSR initiatives have had on Indonesian businesses. The research concludes that CSR institutionalization is crucial to attaining positive CSR outcomes because it facilitates the normalization of social responsibility norms within the business. Long-term success in CSR projects also depends on social capital with stakeholders like local communities and government entities. Aligning CSR initiatives with the SDGs established by the United Nations can boost their impact and help achieve global environmental goals. These results are instructive for Indonesian and other developing-country-based businesses that want to create efficient CSR programs.